Six Cases of the Medial Sural Artery Perforator Flap - Kaoru Kuwabara; Shintaro Ikenoya; Masao Oishi; Asako Yokogi; Noriko Sakakihara; Yui Tanaka (Journal of Plastic and Reconstructive Surgery)
In recent years, the medial sural artery perforator flap has attracted attention due to its thin, pliable, and long vascular pedicle without sacrificing the major vessels of the lower extremities. We encountered six cases of head and neck or limb reconstruction using a medial sural artery perforator flap. All flaps survived; however, one patient developed partial necrosis of the medial head of the gastrocnemius muscle at the donor site. Necrosis of the gastrocnemius muscle does not usually occur after harvesting the medial sural artery perforator flap. However, blood flow to the muscle could decrease after flap harvest. The dissection of the deep surface of the gastrocnemius muscle and between the medial and lateral heads during flap harvest should be minimized to preserve blood flow, and skin grafting should be used when presumable tension is critical.